The methods and algorithms for generating of program trajectories for robotic manipulators of arc welding - M. M. Kozhevnikov; O. A. Chumakov; I. E. Ilushin; L. A. Loboreva (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The new effective methods and algorithms were developed for generating of program trajectories for robotic manipulators of arc welding with account of technological limits. The proposed methods and algorithms, in contrast to the known ones, allow to effectively take into account the shape of the welded seam, as well as the constraints imposed on its orientation. The effectiveness of the developed methods and algorithms is confirmed by the results of experiments with models of robot-manipulators.